Geriatric factors analyses from FFCD 2001-02 phase III study of first-line chemotherapy for elderly metastatic colorectal cancer patients. (March 2017) - Aparicio, Thomas; Gargot, Dany; Teillet, Laurent; Maillard, Emilie; Genet, Dominique; Cretin, Jacques; Locher, Christophe; Bouché, Olivier; Breysacher, Gilles; Seitz, Jean-François; Gasmi, Mohamed; Stefani, Laetitia; et al.
Abstract: Aim: Several predictors of metastatic colorectal cancer (mCRC) outcomes have been described. Specific geriatric characteristics could be of interest to determine prognosis. Method: Elderly patients (75+) with previously untreated mCRC were randomly assigned to receive infusional 5-fluorouracil-based chemotherapy, either alone (FU) or in combination with irinotecan (IRI). Geriatric evaluations were included as an optional procedure. The predictive value of geriatric parameters was determined for the objective response rate (ORR), progression-free survival (PFS) and overall survival (OS). Results: From June 2003 to May 2010, the FFCD 2001-02 randomised trial enrolled 282 patients. A baseline geriatric evaluation was done in 123 patients; 62 allocated to the FU arm and 61 to the IRI arm. The baseline Charlson index was ≤1 in 75%, Mini-Mental State Examination was ≤27/30 in 31%, Geriatric Depression Scale was >2 in 10% and Instrumental Activities of Daily Living (IADL) was impaired in 34% of the patients. Multivariate analyses revealed that no geriatric parameter was predictive for ORR or PFS. Normal IADL was independently associated with better OS. The benefit of doublet chemotherapy on PFS differed in subgroups of patients ≤80 years, with unresected primary tumour, leucocytes >11, 000 mm 3 and carcinoembryonic antigen >2N. There was a trend towards better OS in patients with normal IADL. Conclusion: The autonomy score was an independent predictor for OS. A trend toward a better efficacy of doublet chemotherapy in some subgroups of patients was reported and should be further explored. Highlights: Addition of irinotecan to 5-fluorouracil in the treatment of elderly did not improve progression-free survival and overall survival. Normal autonomy was independently associated with better overall survival (OS). Some patient's subgroup might benefit from doublet chemotherapy with regard to progression free survival (PFS) and overall survival (OS). These sub-group are: age <80, unresected primary tumour, leucocytes >11, 000 and carcinoembryonic antigen >2N for PFS. And patients with normal Instrumental Activities of Daily Living with regard to OS.